The Globalization of Politics - Luard, Evan. author. aut Link
XII, 195 p.
Keywords: The book examines the kind of action that needs to be taken by world bodies in fields such as the trafficing of drugs, international terrorism, world hunger and other pressing problems, and the type of political activity through which individuals can seek to influence them.